2020
DOI: 10.3390/su12093768
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Tryptophan-Like Fluorescence Sensor Concepts for Fecal Exposure Detection in Drinking Water in Remote and Resource Constrained Settings

Abstract: Low-cost, field-deployable, near-time methods for assessing water quality are not available when and where waterborne infection risks are greatest. We describe the development and testing of a novel device for the measurement of tryptophan-like fluorescence (TLF), making use of recent advances in deep-ultraviolet light emitting diodes (UV-LEDs) and sensitive semiconductor photodiodes and photomultipliers. TLF is an emerging indicator of water quality that is associated with members of the coliform group of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Recent efforts are focused on reducing these product costs and enabling continuous in situ water quality monitoring. 99 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent efforts are focused on reducing these product costs and enabling continuous in situ water quality monitoring. 99 …”
Section: Methodsmentioning
confidence: 99%
“…Escherichia coli ( E. coli ) is the most commonly found fecal coliform bacteria and is more specific to human and animal fecal matter, though genome comparisons suggest that some clades of E. coli primarily originate from nonhost natural environments, and there are reports of E. coli detection in pristine areas of tropical and even temperate environments. In recent years, several laboratory-grade products have been validated in the field as predictive of E. coli . , However, these instruments require frequent cleaning, are not intended for long-term autonomous operation, are subject to the drawbacks of methods measuring indicators of fecal contamination and are expensive. Recent efforts are focused on reducing these product costs and enabling continuous in situ water quality monitoring …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor models indicated that currently available T and F fluorescence sensors and turbidity could be used for this purpose. These two sensors have been used in previous efforts for detecting wastewater contamination, ,, although on a more limited scale or different water matrix than the current study. These models, however, were developed using data from laboratory analysis for T and F. Additional work would be needed to understand the steps necessary to translate these models to a field setting.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan fluorescence is facilitated by the indole group attached to the molecule and is often referred to as “Tryptophan‐like fluorescence (TLF)” which encompasses both the amino acid identifier and other compounds, such as free indole, that fluoresce at the same wavelength (Aiken, 2014). In environmental fluorescence spectroscopy, the focus is typically on the wavelengths 280 ex /350–60 em nm as this has been shown to be a proxy for biological activity in water (Box 1) (Baker, 2001; Bedell et al, 2020; Bridgeman et al, 2013; Carstea et al, 2010; Cumberland et al, 2012; Sorensen, Baker, et al, 2018).…”
Section: Recent Developments In Fluorescence Spectroscopymentioning
confidence: 99%